Kepemimpinan Teknokratis Xi Jinping Dalam Mobilisasi Iptek Dan Reformulasi Strategi Pertahanan Indonesia - Budi, Lustia; Priyanto, Yusep; Susilo, Tarsisius; Heri Susanto, Teguh; Firmansah, Rudi (CV RIFAINSTITUT, 2025)
Xi Jinping’s leadership marks a transformation of China’s strategic paradigm from ideological politics to technocratic governance oriented toward innovation in science and technology (S&T) as a foundation of national power. This study aims to analyze the characteristics of Xi’s technocratic leadership in mobilizing science, technology, and the defense industry through the Innovation-Driven Development Strategy (IDDS) and civil–military fusion (CMF) policies, as well as to examine their implications for reformulating Indonesia’s defense strategy and the digitalization of the Indonesian National Armed Forces (TNI). This research applies a qualitative descriptive approach using conceptual and policy analysis based on literature studies from academic sources and official documents. The findings show that Xi’s leadership successfully integrates research, technology, industry, and high-quality human resources into a cohesive and adaptive defense innovation ecosystem. The reflection for Indonesia emphasizes the need to integrate research and strategic industries, strengthen digital defense systems, and develop technocratic human resources to achieve an intelligent and independent defense posture toward Indonesia Emas 2045.